2001
DOI: 10.1063/1.1397763
|View full text |Cite
|
Sign up to set email alerts
|

Indication of ferromagnetism in molecular-beam-epitaxy-derived N-type GaMnN

Abstract: Growth by molecular-beam epitaxy of the dilute magnetic alloy GaMnN is reported. The GaMnN contains 7.0% Mn as determined by Auger electron spectroscopy, and is single phase as determined by x-ray diffraction and reflection high-energy electron diffraction. Both magnetic and magnetotransport data are reported. The results show the anomalous Hall effect, negative magnetoresistance, and magnetic hysteresis at 10 K, indicating that Mn is incorporating into the GaN and forming the ferromagnetic semiconductor GaMnN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
162
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(170 citation statements)
references
References 18 publications
8
162
0
Order By: Relevance
“…Since experimental values for T C in Ga 1−x Mn x N are quite controversial (reported values range from 0K to 940K 4,26,27,28,29,30 ), we refrain from a comparison here. However, the Curie temperatures we calculated are quite low compared to earlier mean-field estimates (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Since experimental values for T C in Ga 1−x Mn x N are quite controversial (reported values range from 0K to 940K 4,26,27,28,29,30 ), we refrain from a comparison here. However, the Curie temperatures we calculated are quite low compared to earlier mean-field estimates (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, available experimental data often contradict each other. Some reports show that high T c ferromagnetism is achievable in this system [2,3,4,5]; others show that the magnetic coupling of the Mn ions in GaMnN is actually antiferromagnetic (AFM) [6]. The exact nature of the magnetism observed in this system is also still under debate [7,8,9].…”
mentioning
confidence: 93%
“…7 Most of these systems are controversially discussed in the literature, and an unambiguous determination of the ferromagnetism has only been reported for (Zn, Cr)Te with a relatively high Cr concentration of 20% and a Curie temperature of 300 K. 8 In particular, in this class of materials (Ga, Mn)N has been frequently mentioned as the most promising high-T C DMS referring to the prediction of model calculations by Dietl et al 5 and ab initio results by Sato et al 9 Many groups have tried to fabricate ferromagnetic (Ga, Mn)N, but the experimental results are very controversial and confusing. After the observation of the ferromagnetism of (Ga, Mn)N, 10 many experiments followed; however, reported T C 's are scattered between 20 and 940 K. [10][11][12][13][14] Moreover, recently Ploog et al observed spin-glass behavior in 7% Mn-doped GaN and suggested that the ferromagnetism observed in 14% Mn-doped GaN originated from Mn-rich clusters. 15 Thus, the ferromagnetism in (Ga, Mn)N is still an open question which we reconsider in this paper.…”
mentioning
confidence: 99%